Fiscal indulgence in Central Europe: loss of the external anchor? - Helge Berger; George Kopits; István P. Székely (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2006)
In recent years, fiscal performance in Central Europe has steadily deteriorated, in contrast to the improvement in the Baltics. This paper explores the determinants of such differences among countries on the path to EU accession. Regression estimates suggest that economic and institutional fundamentals do not provide a full explanation. An alternative explanation lies in the political economy of the accession process, and a game-theoretic model illustrates why a country with a stronger bargaining position might have an incentive to deviate from convergence to the Maastricht criteria. The model generates alternative fiscal policy regimes - allowing for regime shifts - depending on country characteristics and EU policies.
Keywords: H6; C70; 330; Fiscal policy; EU economic and monetary union; game-theoretic approach; Finanzpolitik; EU-Erweiterung; Spieltheorie; Ostmitteleuropa; Nordosteuropa